ANALISIS LIFE CYCLE COST PADA GEDUNG KANTOR BPVP KOTA SORONG - Yunita Lidan; Mandela, Wennie; Andika, Yusverison; Murniyasih, Ery (Construction and Material Journal, 2024)
Building construction requires careful planning and accurate cost estimates. One effective method for calculating costs is the Life Cycle Cost (LCC), which includes the total costs that will be incurred throughout the planned life of the building. Financing consists of planning and construction costs, called initial costs, operational costs, maintenance costs, and demolition costs. This study focuses on the Balai Pelatihan Vokasi dan Produktifitas (BPVP) Sorong City office building, which is undergoing a renovation process. The challenge lies in determining the Life Cycle Cost (LCC) for building maintenance. Analysis of routine and periodic maintenance cost is the method used, with data collected through interviews and data collection from related parties. This study aims to calculate the total cost of the Life Cycle Cost (LCC) and provide recommendations for more efficient cost management in the process. There are four components that underlie the Life Cycle Cost, namely the initial cost or construction cost of Rp.4.703.149.690,60, the operational cost of Rp.128.166.180.245,80, the maintenance cost of Rp.15.698.538.615,10, and the demolition cost of Rp.1.504.632.833.